Zwischen Wissenschaft und autobiographischem Projekt, Saul Friedländer und Ruth Klüger - Machtans, Karolin (Conditio Judaica ;, 2009)
The volume examines the autobiographical texts by Saul Friedländer and Ruth Klüger in the context of their academic work. Both their scholarly and their autobiographical work are subjected to the tension between the opposing poles on the one hand of wishing to approach a reality outside the text and on the other of being aware that every interpretation always depends on the contemporary context and personal background of the interpreter. Thus Friedländer and Klüger approach each other from the two poles of disciplines traditionally opposed to each other - the study of history, directed towards.